A terminological issue: Islamic phılosophy or “phılosophy in the Islamıc world”? - Moris, Megawati (IIUM Press, 2023)
There have been debates and contentions on what should be the term, translated into English, given to the discipline of falsafah or ḥikmah in the Islamic intellectual tradition. Some of the common terms given to it by both Western and Muslim scholars are ‗Islamic philosophy‘, ‗Muslim philosophy‘, ‗Arab philosophy‘ and ‗Arabic philosophy‘. More recently the term ‗philosophy in the Islamic World‘ was made popular by the scholar and philosopher Peter Adamson. The reason for using this term which Adamson considers as a terminological issue is that it is the ―most appropriate‖, and the term Islamic Philosophy is ―too obvious‖. In this paper, firstly, the different terms given to the discipline of falsafah or ḥikmah as aforementioned will be discussed and secondly, why the term ‗Islamic Philosophy‘ is the most precise term to be given to it will be shown. A critique of why the term coined by Adamson is imprecise and does not address the essential meaning of the discipline itself and its role in Islamic civilization will also be undertaken. This issue is of particular significance since using and explaining the correct term would be helpful to clarify how ‗Islamic philosophy‘ is essentially Islamic in its definitions, principles, and characteristics. This counters the common misunderstanding that Islam does not have an authentic philosophical tradition of its own. Understanding the real meaning and role of Islamic philosophy is important to avoid the commonly held view by Muslims and nonMuslims alike that Islam has an anti-intellectual stance which is the cause of violence and extremism among its adherents. Keywords: Terminology, Meaning, Role, Islamic Philosophy, ‗Philosophy in the Islamic world‘.